Evaluasi Efektivitas Program Keperawatan Komunitas dalam Meningkatkan Akses Kesehatan Masyarakat di Wilayah Desa Tapalang Kabupaten Mamuju, Sulawesi Barat Tahun 2024 - Musdalifah, Musdalifah (Barongko: Jurnal Ilmu Kesehatan, 2024)
The implementation of a community nursing program is a crucial strategy for improving access to and quality of health services in rural areas. This study aims to evaluate the effectiveness of the community nursing program in improving public health access in Tapalang Village, Mamuju Regency, West Sulawesi. The research method used a quantitative descriptive approach with a cross-sectional design, involving 100 community respondents selected using purposive sampling. Data were collected through structured questionnaires and field observations, then analyzed using frequency distribution and chi-square tests to examine the relationships between variables. The results showed that the majority of respondents (72%) considered the community nursing program effective in improving access to health services, particularly through outreach activities, home visits, and integrated health posts (Posyandu). The factors most influencing program effectiveness were support from health workers (p=0.001), availability of infrastructure (p=0.004), and community participation (p=0.012). This study concluded that the community nursing program in Tapalang Village was quite effective in improving health access, although challenges related to limited staff and facilities remained. It is recommended that cross-sector collaboration, ongoing training for community nurses, and strengthening community participation be improved to ensure the program's sustainability.